“A hard-won capability”: the experiences of parents managing their babies' medicines after discharge from a neonatal unit - Bracken, Louise; Clark, Janet; Gill, Andrea; O'Brien, Fiona; Dewey, Rachael; Barker, Catrin; Carter, Bernie (Frontiers in Communication, 2023)
Parents of babies who required neonatal care are responsible for managing their medicines after they are discharged home. There is wide variation in the information and amount of preparation given to parents prior to assuming this challenging task.The aim of the Parent co-Designed Drug Information for parents and Guardians Taking Neonates home (PADDINGToN) study was to explore parents' experiences of managing their babies' medicines post discharge from a neonatal unit and to use this information to develop suitable resources for future families.A qualitative participatory interpretative approach using a mixture of remote and face-to-face small group interviews or one-to-one interviews was used. Parents were recruited using social media advertisements and convenience sampling from five study sites (four neonatal units in England and one in Ireland). Parents from other neonatal units were invited to take part through social media advertisement. The interviews were audio-recorded and inductive reflexive thematic analysis was used to analyse the data.Seventeen parents (14 mothers, 3 fathers) participated. One over-arching theme, 'A hard won capability', and four major interpretive themes were generated from the analysis of the data: Being in NICU and the prospect of going home: emotional and practical challenges; Living the reality of being at home: the uncertainty associated with giving medicines; Being at home: battling the system and a lack of support/knowledge; and Suggesting ways forward: parents' lived insights into improving information and resources.Despite the challenges they faced, parents developed strategies for safely and reliably managing medicines administration and they assimilated knowledge, built their confidence and achieved a capability in medicines administration. Their experiences have been used to build a suite of medicines administration resources to support future parents.